Use of Hypertonic Saline in Neuroanesthesia and Neurocritical Care Practice: A Narrative Review - Barik, Amiya K.; Thappa, Priya; Jangra, Kiran; Bhagat, Hemant; Kaur, Kirandeep (Journal of Neuroanaesthesiology and Critical Care, 2023)
Hypertonic saline (HTS) is a group of fluids containing sodium and chloride in a higher concentration as compared to physiological saline. The authors have conducted this review to evaluate the use of HTS in neuroanesthesia and neurocritical care. The articles for this narrative review on HTS were searched on databases like PubMed Central, EMBASE, and Google Scholar using the Medical Subject Headings keywords “Hypertonic Saline,” “Neuroanesthesia,” and “Neurocritical Care.” The review focuses on the mechanisms of HTS and its in routine clinical practice. The results of various comparative studies between HTS and mannitol and guidelines regarding the use of HTS have also been reviewed. HTS can be used to treat hyponatremia, reduce intracranial pressure, provide intraoperative relaxed brain, and aid in resuscitation during cardiogenic, neurogenic, and septic shock. Its side effects include renal toxicity in the case of hypernatremia, rebound intracranial hypertension, volume overload, dyselectrolytemia, phlebitis, local tissue damage, and osmotic demyelination syndrome in the case of rapid correction of serum sodium concentration.
Keywords: hypertonic saline; neuroanesthesia; neurocritical care